Visualisation of xanthan conformation by atomic force microscopy. (5th September 2016) - Moffat, Jonathan; Morris, Victor J.; Al-Assaf, Saphwan; Gunning, A. Patrick
Highlights: New AFM imaging methodology BlueDrive™ enabling resolution of xanthan's helix. Visual evidence of the structural composition of xanthan's helices. Confirmation of the effect of counterion screening on structural ordering. Abstract: Direct visual evidence obtained by atomic force microscopy demonstrates that when xanthan is adsorbed from aqueous solution onto the heterogeneously charged substrate mica, its helical conformation is distorted. Following adsorption it requires annealing for several hours to restore its ordered helical state. Once the helix state reforms, the AFM images obtained showed clear resolution of the periodicity with a value of 4.7 nm consistent with the previously predicted models. In addition, the images also reveal evidence that the helix is formed by a double strand, a clarification of an ambiguity of the xanthan ultrastructure that has been outstanding for many years.